ANALISIS PROFITABILITAS DAN PENGARUHNYA TERHADAP TINGKAT PERTUMBUHAN BERKELANJUTAN PADA KOPKAR PT TELKOM MAKASSAR - Ahmad Musseng (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
This research is aimed to explain the cause of factors in decreasing company’s profitability rate, and explain the most dominant factors affecting the profitability of company in which taken the case on Kopkar PT Telkom at Makassar. The benefits are as in input for making the decision managerial level in increasing the profitability of the company and as a reference for another research.The first time is using financial ratio’s analysis to see the growth trend from every loss/profit account, to watch the company sustainable growth rate for five recent years (2006-2010) and the relationship for component used by regression and correlation analysis. The result are the factor affecting company profitability caused by significant increasing in component of sales base price, marketing cost and administration and general expenses for five recent years. The most dominant factors and administration and general expenses. All factors reflected by profit margin along with assets turnover affect the rate of ROI which is lower for five recent years. The correlation between ROI’s variable reflected by profit margin on total assets turnover together with company’s sustainable growth rate showing strong correlation because the coefficient of determination (R2) are 0,780 (78%) and the rest 22% are from other factors. In determining the success of a business management governance is largely determined and analyzed periodically to determine the rate of growth performance in laying down policy